Birds at Eucalyptus and other flowers in Southern Brazil: A review - Willis, Edwin O. [UNESP] (My University, 2002)
In southern Brazil, I recorded 14 species of hummingbirds, one woodpecker, three Psittacidae, four Tyrannidae, one mockingbird, and 31 tanagers and relatives at eucalyptus flowers. Others have registered 3 different hummingbirds, another parrotlet, four more tyrannids, a peppershrike, a thrush, and 5 tanagers and related birds, for a total of 69 species. However, commercial plantations rarely flower, so use is local or undependable. Understory Phaethorninae are not recorded at eucalyptus, rarely at other tall and hence multiflowered trees. Bromelias and other flowers are noted in various studies, which add 89 species of flower feeders, including 14 Psittacidae, 17 Trochilidae, and 37 tanagers and relatives. Isolated low flowers and epiphytes are mostly visited by hummingbirds (some by Coereba), but some tall trees (Chorisia) also. As two times as many tanager species visit flowers as hummingbirds, researchers will have to get up early and patiently study treetop and nonpatchy habitats. However, tree plantations can attract artificially, like feeders. Bunch-flowering extrafloral nectar (Mabea, Combretum) is preferred by wandering mixed-flock treetop or edge tanagers and relatives, which often crawl over bunched flowers like parrots or woodpeckers (or marsupials and other mammals) rather than hover at separate flowers like nonflocking Trochilidae or peck from nearby like Nectariniidae and Coereba. Clamberers and petal-pullers, even nectar robbers, can cause evolution of umbels and other bunched flowers, for the bird, mammal or insect receives pollen from nearby flowers. Psittacidae, saltators and others mostly eat flowers, but can pollinate if they touch nearby flowers. Multiflowered trees can also attract hawks, causing waves of tanagers, parrots and others that move on to pollinate trees via fear and nectarivory. Certain groups, notably thrushes and tyrannids, seem to use nectar little, the latter often catching insects.
Keywords: Emberizidae; Eucalyptus; Flowers; Hummingbirds; Psittacidae; Southern Brazil; Tanagers; Accipitrinae; Aves; Chorisia; Coereba; Combretum; Emberizinae; Hexapoda; Mabea; Mammalia; Metatheria; Nectariniidae; Picidae; Trochilidae; Turdidae; Tyrannidae